Biological oceanographic processes - Parsons, Timothy R. (Butterworth-Heinemann, 1995)
his popular undergraduate textbook offers students a firm grounding in the fundamentals of biological oceanography. As well as a clear and accessible text, learning is enhanced with numerous illustrations including a colour section, thorough chapter summaries, and questions with answers and comments at the back of the book.